2020
DOI: 10.1080/20018525.2020.1840706
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable benefits of intravenous immunoglobulin (IVIG) in a patient with polymyositis-associated acute interstitial lung disease

Abstract: Polymyositis (PM) and dermatomyositis (DM) are subtypes of autoimmune inflammatory myopathies. Interstitial lung disease (ILD) involvement is common in PM/DM. There is no evidence base for immunosuppression in DM/PM-ILD and current evidence is based on case stories and expert opinions. We present a 63-year-old male with severe respiratory failure due to PM-ILD who was treated successfully with intravenous immunoglobulin, recovered the acute phase and survived more than 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Sarah Gee et al reported some immunity system alterations in neonates born to mothers with recent or ongoing SARS-CoV-2 infection, one of which is the reduced transfer of SARS-CoV-2-specific IgG to neonates due to impaired placental antibody transfer [29] . Taking this into account along with IVIG mechanisms of action [27] , [30] and its effectiveness in viral clearance, radiologic remission and clinical improvement [31] , [32] , [33] , it seems that the IVIG administration played an important role in viral clearance, radiologic remission and clinical improvement of our patient as well.…”
Section: Discussionmentioning
confidence: 70%
“…Sarah Gee et al reported some immunity system alterations in neonates born to mothers with recent or ongoing SARS-CoV-2 infection, one of which is the reduced transfer of SARS-CoV-2-specific IgG to neonates due to impaired placental antibody transfer [29] . Taking this into account along with IVIG mechanisms of action [27] , [30] and its effectiveness in viral clearance, radiologic remission and clinical improvement [31] , [32] , [33] , it seems that the IVIG administration played an important role in viral clearance, radiologic remission and clinical improvement of our patient as well.…”
Section: Discussionmentioning
confidence: 70%
“…Previously published case reports have shown beneficial effects of IVIG. A patient with severe respiratory failure due to Anti-Jo1 AS-ILD who was treated successfully with intravenous immunoglobulin, recovered from the acute phase and remained stable for years [ 8 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“… Study Type Disease Number of patients IVIG dosage Co-medications Outcome Peshbahar et al. [ 8 ] Case report Anti-Jo-1 AS-ILD 1 30g, 12 week intervals CS and AZA Recovering acute phase, survived >4 years Huapaya et al. [ 9 ] Retrospective study Anti Jo-1, PL-7, PL-12 and EJ AS-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is biologic plausibility for the treatment of IIM-ILD/AS-ILD or anti-MDA5+ ILD with IVIG and PEX, there is limited evidence [62–64]. However, they may have less risk of infection compared with other regimens.…”
Section: Treatmentmentioning
confidence: 99%